Integration of Multi-Index Method and Qual2kw Evaluation Modeling of Quality Status and Pollutant Dispersion Pattern of Perian River in Kutai Kartanegara - Dwi Fitria Sari; Taufik Hamdani; Syelvialousiana Ningsih Kalauw; Rina Ermawati; Rudi Kartika; Slamet Ningsih Hadi Raharjo (Jurnal Beta Kimia, 2026)
This study is intended to assess water quality and determine the pollution status of the Perian River in its upstream (Perian Village) and downstream (Muara Aloh Village) sections in 2025. (COD) parameters. The findings reveal a marked deterioration in water quality from the upstream to the downstream segment of the river. Based on the CCME- WQI, both locations were categorized as "Poor," with scores of 61.95 (upstream) and 57.20 (downstream). The STORET method classifies the upstream status as "Moderately Polluted" (-23) and the downstream as "Heavily Polluted" (-42). Meanwhile, the PI method assigned a "Lightly Polluted" status to both locations. High concentrations of Nitrate (up to 42.57 mg/L) and Fecal Coliform (up to 12,976 counts/100ml) were the primary contributors to water quality degradation. The total actual COD pollution load was 25,344.52 kg/day, with the upstream area contributing a dominant share of 70.09%. Stringent conservation efforts and waste management along the river are required to prevent further degradation. This study also applied pollutant dispersion modeling using the Qual2Kw method.